Needs analysis for program developing emotional intelligence of nursing students: a qualitative study - Kucuk Yuceyurt, Nil; Kaya, Hulya (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the emotional intelligence training programme needs of nursing students. Method: The qualitative study was conducted from December 2018 to July 2020 after approval from the ethics review committee of Istanbul University-Cerrahpasa, Turkiye. Data was collected between January 2019 and May 2020 using in-depth individual interviews with stakeholders of nursing education, including nurse educators, hospital nurses, nursing students, and patients. The data collected was subjected to thematic analysis. Results: Of the 25 subjects, 3(12%) were nurse educators, 7(28%) were hospital nurses, 10(40%) were nursing students, and 5(20%) were patients. On the basis of the data collected, 4 main themes were identified; expectations, educator and student responsibilities, emotional intelligence skills, and developing emotional intelligence skills. There were 11 sub-themes within the main themes. The participants revealed that they expected nursing students and nurses to have advanced skills in terms of emotional intelligence. Conclusion: Emotional intelligence skills are an indispensable part of nursing, and represent a priority in professional development. According to nursing education stakeholders, nursing students were not sufficiently competent in terms of the skills constituting the sub-dimensions of emotional intelligence. Key Words: Education, Nursing, Emotional intelligence, Students, Nursing.